Anti-WebShell PHP Backdoor Scanner pada Linux Server - Christian Ronaldo Sopaheluwakan; Dian Widiyanto Chandra (Teknik Informatika Fakultas Ilmu Komputer Univeristas Muslim Indonesia, 2020)
Backdoor or commonly also known as web shell is one of the malicious software that hackers use to maintain access systems that they have entered. Relatively few programs like Anti Web-Shell, PHP Backdoor Scanner circulating on the Internet, and can be obtained free of charge to deal with the issues above. But most of these programs have no actual database of signature behavior to deal with PHP backdoor / Shell nowadays. Then comes the contemporary Anti Web-Shell program that can deal with today's backdoor shell. This study uses an experimental method concerning previous similar studies and is implemented directly into the world of cyber security professional industries. By enriching the Regex dictionary signature and String Array Matching the actualized Anti Web-Shell program can detect more backdoor than similar programs that have existed in the past. The results of this study are in the form of a web application software in PHP extension. The application can minimize 100% of false positives and is twice as fast in scanning files because it is more specific in heuristic analysis scan.